Content of Rare Earth Elements in Flos Sophorae from Different Areas - Li, Yumei (Asian Journal of Chemistry, 2011)
Today more and more attention has been paid to the rare earth elements (REEs) in Chinese traditional medicine. Flos sophorae, a traditional Chinese medicinal herb, was collected from 11 areas of Dezhou and analyzed by ICP-MS to study the content and distribution of 14 kinds of rare earth elements. The results showed that ICP-MS is accurate, reliable technique for determining rare earth elements in the Chinese medicinal herbs because of its low detection limit and accuracy and the method was verified by GBW07605. The contents of total rare earth elements in flos sophorae samples from different areas ranged from 1.2077 to 2.4742 μg/g and the determined content of rare earth elements in flos sophorae varied from one area to another. The plot of normalized element concentration versus atomic number showed some characteristic distribution tendencies. The distribution tendency of light rare earth elements (La-Gd) was relatively flat except a positive Eu anomaly, however, the distribution tendency was steep and discrepant for heavy rare earth elements (Tb-Lu). The results provided a reference for study relationship between the content of rare earth elements and curative mechanism, the pharmacology characteristics and its geology condition.